Artificial intelligence and the planning task - Ache, Peter (AESOP, 2025)
The article reflects on the planning task in the context of artificial intelligence, offering a forward-looking perspective for the next decade. It begins by revisiting debates on planetary urbanisation and the implications of techno-scientific urbanism, particularly through smart city initiatives and data-driven governance. Ache critically examines AI’s reliance on large datasets, its tendency to reinforce normative patterns, and its entanglement with corporate power structures. The text then explores how AI systems intersect with material infrastructures, environmental burdens, labour exploitation, and global socio-economic inequalities. Case studies—from smart home technologies to large-scale AI computing facilities—highlight ethical dilemmas, energy consumption, pollution, and uneven spatial impacts. The article calls for clearer rules of engagement, countervailing civic powers, and more progressive, democratically informed approaches to technology. Ache draws on thinkers such as Acemoglu, Naughton, and Bridle to argue for broader, more inclusive understandings of intelligence that extend beyond computational models. The piece concludes by inviting reflection on future urban imaginaries and the role of planners, emphasising curiosity, criticality, and human-centred perspectives.
plaNext – Next Generation Planning, 15 (2025)
Keywords: artificial intelligence; planning task; urban futures; techno-scientific urbanism; smart cities